CXCL5 suppression recovers neovascularization and accelerates wound healing in diabetes mellitus - Ching Chen; Liang-Yu Lin; Jaw-Wen Chen; Ting-Ting Chang (Cardiovascular Diabetology, 2023)
Abstract Background Higher chemokine C-X-C motif ligand 5 (CXCL5) level was observed in type 2 diabetes mellitus (DM) patients; however, its role in diabetic vasculopathy was not clarified. This study aimed to explore the impacts and mechanistic insights of CXCL5 in neovasculogenesis and wound healing in DM. Methods Endothelial progenitor cells (EPCs) and human aortic endothelial cells (HAECs) were used in vitro. Streptozotocin-induced diabetic mice and Leprdb/JNarl mice were used as type 1 and type 2 DM models. Moreover, CXCL5 knockout mice were used to generate diabetic mice. Hindlimb ischemia surgery, aortic ring assays, matrigel plug assay, and wound healing assay were conducted. Results CXCL5 concentrations were increased in plasma and EPCs culture medium from type 2 DM patients. CXCL5 neutralizing antibody upregulated vascular endothelial growth factor (VEGF)/stromal cell-derived factor-1 (SDF-1) and promoted cell function in EPCs from type 2 DM patients and high glucose-treated EPCs from non-DM subjects as well as HAECs. CXCL5 directly up-regulated interleukin (IL)-1β/IL-6/tumor necrosis factor-α and down-regulated VEGF/SDF-1 via ERK/p65 activation through chemokine C-X-C motif receptor 2 (CXCR2). CXCL5 neutralizing antibody recovered the blood flow after hindlimb ischemia, increased circulating EPC number, and enhanced VEGF and SDF-1 expression in ischemic muscle. CXCL5 suppression promoted neovascularization and wound healing in different diabetic animal models. The above observation could also be seen in streptozotocin-induced CXCL5 knockout diabetic mice. Conclusions CXCL5 suppression could improve neovascularization and wound healing through CXCR2 in DM. CXCL5 may be regarded as a potential therapeutic target for vascular complications of DM.